The Effect of Glutathione on Serum Malondialdehyde (MDA) Level in Retinopathy of Prematurity Rat Models - Puspita Kusuma Dewi (Diponegoro University, 2020)
Introduction Retinopathy of prematurity (ROP) is the leading cause of blindness in newborn babies worldwide. The benefit of anti-oxidant was investigated for ROP cases by assessing its effect on the oxidative stress of the tissues. Glutathione is a primary endogenous in human body and its supplementation has been discovered for its benefits towards some ocular diseases. This study aims to understand the effect of glutathione on oxidative stress marker, serum Malondialdehyde (MDA), in ROP rat models.